The effect of applying International Accounting Standard 12 (income taxes) in the activation of the tax system - Baban Mahmoud; Ramyar Ahmed (گۆڤارا زانستێن مرۆڤایەتی یا زانكۆیا زاخۆ, 2023)
The study aims to diagnose the effect of applying International Accounting Standard 12 (income taxes) on tax accounting processes on the one hand, and to identify the reflection of the financial statements as a mediating variable in the relationship between International Accounting Standard 12 (income taxes) as an independent variable and the approved variable for tax accounting. In order to answer these questions, the tax departments were selected as well as a sample of academics specialized in the field of accounting and tax accounting at the University of Sulaymaniyah in the Kurdistan Region - Iraq as a field of study and a source for obtaining the data collected by the questionnaire distributed to a sample of professionals working in the tax departments as well as a sample of Academics specialized in the field of accounting and tax accounting, numbering (127), from which (100) valid forms were retrieved for statistical analysis. The questionnaire was used to collect the required data  to analyze it in order to reach the results of the study in both its theoretical and practical aspects. A hypothetical scheme was formulated that reflects the harmonious relationships and influence between the dimensions of the study, which are (International Accounting Standard 12 (income taxes), financial statements, and tax accounting). objectives and implementation of its plan. The field verification was consistent with the theoretical objective, which proved the existence of relationships between the dimensions studied. The study reached a set of conclusions, the most important of which is the existence of an impact relationship for International Accounting Standard 12 (income taxes) in activating tax accounting with the presence of financial statements. In light of the conclusions reached by the study, a number of proposals were presented, the most important of which is related to the need for timing decisions to expand attention and focus more on applying International Accounting Standard 12 (income taxes) to better activate tax accounting processes.